2018
DOI: 10.1002/cncr.31304
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety results of depatuxizumab mafodotin (ABT‐414) in patients with advanced solid tumors likely to overexpress epidermal growth factor receptor

Abstract: BACKGROUNDEpidermal growth factor receptor (EGFR) alterations are associated with multiple cancers. Current EGFR‐directed therapies have led to increased efficacy but are associated with specific side effects. The antibody‐drug conjugate depatuxizumab mafodotin (depatux‐m) targets EGFR with a monoclonal antibody linked to a cytotoxin, and is highly tumor‐specific.METHODSThis phase 1/2 study evaluated the safety, pharmacokinetics, and efficacy of depatux‐m in patients who had advanced solid tumors with known wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 27 publications
2
59
0
Order By: Relevance
“…Prophylactic use of steroid eye drops is another approach that has been reported to be successful in reducing the frequency and severity of ocular events in trials of other ADCs, such as ABT-414 and SGN-CD19A (both of which utilize MMAF as their cytotoxic payload; refs. [28][29][30]. The actual mechanism(s) by which steroids can reduce ADC-induced keratopathy remain poorly defined and, as supported by our preclinical modeling, there appears to be no inflammatory component underlying the etiology of the corneal toxicity observed with mirvetuximab soravtansine.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Prophylactic use of steroid eye drops is another approach that has been reported to be successful in reducing the frequency and severity of ocular events in trials of other ADCs, such as ABT-414 and SGN-CD19A (both of which utilize MMAF as their cytotoxic payload; refs. [28][29][30]. The actual mechanism(s) by which steroids can reduce ADC-induced keratopathy remain poorly defined and, as supported by our preclinical modeling, there appears to be no inflammatory component underlying the etiology of the corneal toxicity observed with mirvetuximab soravtansine.…”
Section: Discussionmentioning
confidence: 72%
“…The more modest effects on blurred vision suggest that additional mechanisms, less influenced by steroid prophylaxis, are likely contributing to this symptom in patients. Of interest, in the ADC studies where steroid prophylaxis has been shown to be effective, the ocular AEs were more severe at onset (grades 3 or 4) and were subsequently reduced to grade 1/2 events (27)(28)(29)(30), comparable with the baseline levels seen with mirvetuximab soravtansine. Prophylactic steroid eye drop use as a mitigation strategy has not eliminated ADC-induced keratopathy, and it is reasonable to suggest that there is a role for additional strategies to further optimize ADC-related ocular AE profiles.…”
Section: Discussionmentioning
confidence: 93%
“…As a result of deletion, EGFR vIII is unable to bind known ligands and shows enhanced stability in cell membrane. [116] extracellular vesicles (EVs), the fact that extrachromosomal amplicons may be transported between cells is gaining importance [120]. erefore, in such a context, the role of amplicons is not to increase oncogene mRNA levels, but rather to enable more flexible regulation of gene expression as well as transfer of mutated gene to cells initially lacking such alteration.…”
Section: Egfr VIII Alteration In Cancermentioning
confidence: 99%
“…Depatuxizumab mafodotin is an anti-EGFR ADC targeting a tumor-selective cryptic epitope on the CR1 domain of EGFR [98]. Probably as a result of the tumor selectivity, depatuxizumab mafodotin did not cause dose-limiting dermatological adverse events or diarrhea characteristic of other anti-EGFR therapies, even though EGFR is broadly expressed in normal tissues [99]. Similar to the cases of the anti-HER2 ADCs, the development of the anti-EGFR ADC suggests that the technical hurdles associated with ADC targets may be overcome by taking advantage of the target biology in the context of cancer cells.…”
Section: Target Antigensmentioning
confidence: 99%